Comparing shariah with law: methodological complexity in the modern context - Haneef, Sayed Sikandar Shah; Abdul Razak, Mohd Abbas; Laluddin, Hayatullah (Lexis Nexis, 2020)
Comparing Shariah with law is a common practice both in the Shariah and law schools. There are various levels of comparison from a simple curiosity to find the differences and similarities between Shariah and a positive legal system, whether Common Law or Civil Law, to a more advanced level of comparing legal postulates and concepts in the two systems in order to harmonise and reconcile the two. Depending on the purposes, methodology also differs: mere comparison between a statutory law and fiqh, conducting a thorough analysis of the two systems in terms of origins, sources and practical applications, and conceptual analysis beyond language similarities. In consequence, in terms of end-goal, there has been divergent approaches to the harmonization of Law with Shariah containing even skewed views. To remedy this, this article argues for methodological comparison between the two so as to overcome the problem of paradoxical approaches in comparative studies on topical issues like human rights.